SOCIETY AND CULTURE IN USA, UK AND UZBEKISTAN - Nuriddinova Sevinchgul Orzu qizi; Hakima Botirova (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Capturing the essence of society and culture in these three diverse nations is akin to embarking on a mesmerizing cultural odyssey. While the USA, UK, and Uzbekistan each boast unique features, they converge in their celebration of tradition, the dynamism of societal shifts, and the ever-present influence of global interconnectedness. Exploring their tapestries reveals the rich interconnectedness of our global society, an interplay of histories, traditions, and values that continues to shape our world in myriad magical ways.